Influence of green marketing practices on purchase intention among millennials in Lima Metropolitan Area (Peru), 2023 - Salas-Canales, Hugo Jesús (2024)
In the contemporary context of the 21st century, it is imperative to recognize the relevance of green marketing practices as a fundamental tool to attract and engage the consumer generation known as millennials. These individuals are characterized by their high environmental awareness and commitment to sustainability, increasingly seeking products and services that reflect their ecological values. The main objective of this research was to determine how these practices influence the purchase intention of millennials residing in Lima Metropolitan Area. To address this question, a quantitative approach was employed through a non-experimental cross-sectional correlational-causal research design. The sample consisted of 385 participants born between 1980 and 1995, residing in various districts of Lima Metropolitan Area, who were administered a questionnaire based on the Likert scale. The results confirmed the existence of a causal relationship between green marketing practices and purchase intention, supported by the analysis of the Nagelkerke coefficient, which yielded a value of 0.766 (76.6%).